Recombinant TgHSP70 Immunization Protects against Toxoplasma gondii Brain Cyst Formation by Enhancing Inducible Nitric Oxide Expression - Czarnewski, Paulo; Araújo, Ester C. B.; Oliveira, Mário C.; Mineo, Tiago W. P.; Silva, Neide M. (Frontiers in Cellular and Infection Microbiology, 2017)
Toxoplasma gondii is known to cause congenital infection in humans and animals and severe disease in immunocompromised individuals; consequently development of vaccines against the parasite is highly necessary. Under stress conditions, T. gondii expresses the highly immunogenic heat shock protein 70 (TgHSP70). Here, we assessed the protective efficacy of rTgHSP70 immunization combined with Alum in oral ME-49 T. gondii infection and the mechanisms involved on it. It was observed that immunized mice with rTgHSP70 or rTgHSP70 adsorbed in Alum presented a significantly reduced number of cysts in the brain that was associated with increased iNOS+ cell numbers in the organ, irrespective the use of the adjuvant. Indeed, ex vivo experiments showed that peritoneal macrophages pre-stimulated with rTgHSP70 presented increased NO production and enhanced parasite killing, and the protein was able to directly stimulate B cells towards antibody producing profile. In addition, rTgHSP70 immunization leads to high specific antibody titters systemically and a mixed IgG1/IgG2a response, with predominance of IgG1 production. Nonetheless, it was observed that the pretreatment of the parasite with rTgHSP70 immune sera was not able to control T. gondii internalization and replication by NIH fibroblast neither peritoneal murine macrophages, nor anti-rTgHSP70 antibodies were able to kill T. gondii by complement-mediated lysis, suggesting that these mechanisms are not crucial to resistance. Interestingly, when in combination with Alum, rTgHSP70 immunization was able to reduce inflammation in the brain of infected mice and in parallel anti-rTgHSP70 immune complexes in the serum. In conclusion, immunization with rTgHSP70 induces massive amounts of iNOS expression and reduced brain parasitism, suggesting that iNOS expression and consequently NO production in the brain is a protective mechanism induced by TgHSP70 immunization, therefore rTgHSP70 can be a good candidate for vaccine development against toxoplasmosis.